2007
DOI: 10.1073/pnas.0607817104
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aspartoacylase, the brain enzyme impaired in Canavan disease

Abstract: Aspartoacylase catalyzes hydrolysis of N-acetyl-L-aspartate to aspartate and acetate in the vertebrate brain. Deficiency in this activity leads to spongiform degeneration of the white matter of the brain and is the established cause of Canavan disease, a fatal progressive leukodystrophy affecting young children. We present crystal structures of recombinant human and rat aspartoacylase refined to 2.8-and 1.8-Å resolution, respectively. The structures revealed that the N-terminal domain of aspartoacylase adopts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
121
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 70 publications
2
121
0
1
Order By: Relevance
“…Finally, the distance between the sulfur atoms of Cys124 and Cys152 is 5. 5 Å (Bitto et al 2007), which means they are close enough for the formation of a disulfide bridge. Future studies would benefit from the proposed homology model and proposed catalytic mechanism, as well as the available crystal structure for drug design with the goal of restoring ASPA activity in CD patients with catalytically deficient ASPA enzyme (Qiao et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the distance between the sulfur atoms of Cys124 and Cys152 is 5. 5 Å (Bitto et al 2007), which means they are close enough for the formation of a disulfide bridge. Future studies would benefit from the proposed homology model and proposed catalytic mechanism, as well as the available crystal structure for drug design with the goal of restoring ASPA activity in CD patients with catalytically deficient ASPA enzyme (Qiao et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this manuscript, a report was published which confirms our proposal that ASPA contains a single zinc atom (Le Coq et al 2006). When this manuscript was in the process of review, the X-ray crystal structures of rat and human ASPA were published (Bitto et al 2007). Upon comparing our homology model of the active and binding sites of ASPA with those of the published crystal structure, the root-mean-square deviations between C α atoms is 1.1 Ǻ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sequence of human aspartoacylase is only ~10% identical with that of bovine carboxypeptidase A (CPA) (8). A structural comparison of rat aspartoacylase with CPA found that the C-terminal domain of aspartoacylase is not present in carboxypeptidase, while the Nterminal domain of CPA is approximately 60 residues longer than the corresponding domain of aspartoacylase (10).…”
mentioning
confidence: 99%
“…This classification is supported by recent work in which aspartoacylase was shown to bind one zinc ion per monomer (9), consistent with its assignment to the zinc carboxypeptidase family. Recently, the crystal structures of the rat form and the human form of aspartoacylase have been determined at 1.8 and 2.8 Å resolution, respectively, by the Center for Eukaryotic Structural Genomics (10). Both of these structures are the apo form of the enzyme that was crystallized in the absence of either substrates or products.…”
mentioning
confidence: 99%
See 1 more Smart Citation